2015
DOI: 10.5812/jjm.21468
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole Resistance Candida albicans in Females With Recurrent Vaginitis and Pir1 Overexpression

Abstract: Background:Some genes may be associated with Candida albicans resistance to azoles. Pir1 gene is described as responsible to induce resistance in C. albicans.Objectives:The current study aimed to find the relationship between fluconazole resistance and Pir1 protein (Pir1p) overexpression in the females with recurrent C. albicans vaginitis requiring longer fluconazole therapy.Patients and Methods:A total of 52l vaginal samples were obtained from the females with C. albicans vaginitis. The azole susceptibility p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In Cameroon, more than half of Candida yeasts were resistant to fluconazole in 2012 (Gonsu Kamga et al, 2014). Elsewhere in the world, high C. albicans resistance to azoles has been reported by several authors (Bagg et al, 2005;Chryssanthou, 2001;Nasrollahi et al, 2015;Sandra et al, 2005). These high rates of antifungal resistance provide good reason for regular monitoring of C. albicans susceptibility to these drugs to ensure effective treatment of candidosic lesions.…”
Section: Discussionmentioning
confidence: 93%
“…In Cameroon, more than half of Candida yeasts were resistant to fluconazole in 2012 (Gonsu Kamga et al, 2014). Elsewhere in the world, high C. albicans resistance to azoles has been reported by several authors (Bagg et al, 2005;Chryssanthou, 2001;Nasrollahi et al, 2015;Sandra et al, 2005). These high rates of antifungal resistance provide good reason for regular monitoring of C. albicans susceptibility to these drugs to ensure effective treatment of candidosic lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Fluconazole basically alters the cellular membranes which leads to increased membrane permeability, impaired uptake of precursor, and leakage of essential elements from the cell (Charlier et al 2006). However, Nasrollahi et al (2015) reported resistance of C. albicans to fluconazole since Pir1p, a protein responsible for cell wall maintenance, was found overexpressed in the fungal cell wall due to prolonged fluconazole treatment. Moreover, another triazole examined in the present study was voriconazole, a second-generation triazole and a synthetic derivative of fluconazole.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, C. glabrata is the second most common causative agent of invasive candidiasis (12-18%), reportedly exhibiting resistance against fluconazole [16]. An earlier study reported that approximately 94% of all C. albicans isolates from vaginitis patients exhibit resistance to fluconazole [17]. Furthermore, another study has reported that certain Candida isolates exhibit resistance to fluconazole and econazole [18].…”
Section: Introductionmentioning
confidence: 99%